Finding Islam in Cinema: Islamic Films and the Identity of Indonesian Muslim Youths - H. Hariyadi (Al-Jami'ah: Journal of Islamic Studies, 2013)
This paper discusses Islamic films in Indonesia that have been a phenomenon since a decade. It is reported that Islamic films have been consciously produced to propagate Islamic lessons to the Muslim youths. The paper challenges the notion that young adults are passive recipients as proposed by some popular culture theorists. They did not merely become object of ideologies injected by filmmakers, and their responses were not an unquestioning acceptance. The research found that some Muslim youths have been ambiguous toward the emergence of Islamic films. Watching movie for Indonesian youths is an important way to construct identity, and they feel that there is a sense of religious ritual involved in film viewing, especially with Islamic messages. I argue that Islamic films help Indonesian young people to develop their own distinctive identity, being new sources of authority apart from parents, formal education, and friends.[Tulisan ini membahas film islami di Indonesia yang menjadi fenomena sejak satu dekade terakhir. Film-film islami sengaja dibuat untuk menyebarkan ajaran Islam dengan sasaran kalangan muda. Makalah ini menolak gagasan bahwa remaja adalah penerima pasif seperti yang diajukan oleh teori budaya popular. Mereka tidak hanya menjadi objek desakan ideologi pembuat film dan mereka juga tidak bisa menerimanya secara bulat. Sebagian pemuda muslim merasa ambigu menghadapi munculnya film-film Islam. Di sisi lain, menonton film menjadi media untuk membangun identitas diri dan dapat dirasakan sebagai bagian dari ritual agama, khususnya ketika menonton film yang mengandung pesan-pesan Islam. Dengan demikian, film Islam membantu pemuda Indonesia untuk mengembangkan identitas mereka sendiri dan menjadi sumber otoritas baru di luar orang tua, pendidikan formal, dan lingkungan pergaulan.]